Random Whole Body Vibration over 5 Weeks Leads to Effects Similar to Placebo: A Controlled Study in Parkinson’s Disease - Heiko Gaßner; Annette Janzen; Ansgar Schwirtz; Petra Jansen (Parkinson's Disease)
Background. Random whole body vibration (WBV) training leads to beneficial short-term effects in patients with Parkinson’s disease (PD). However, the effect of WBV lasting several weeks is not clear. Objectives. The aim of this study was to assess a random WBV training over 5 weeks in PD. Methods. Twenty-one participants with PD were allocated to either an experimental or a placebo group matched by age, gender, and Hoehn&Yahr stage. The WBV training consisted of 5 series, 60 s each. In the placebo group, vibration was simulated. The primary outcome was the change of performance in Functional reach test (FRT), step-walk-turn task, biomechanical Gait Analysis, Timed up and go test (TUG), and one leg stance. Findings. In most of the parameters, there was no significant interaction of “time*group.” Both groups improved significantly in Gait parameters, TUG, and one leg stance. Only in the FRT [F(1,15)=8.397; P<0.05] and in the TUG [F(1,15)=4.971; P<0.05] the experimental group performed significantly better than the placebo group. Conclusions. Random WBV training over 5 weeks seems to be less effective than reported in previous studies performing short-term training. The slight improvements in the FRT and TUG are not clinically relevant.